The Effect of Temporary Syirkah Funds and Other Comprehensive Income on the Capital Performance of Bank Syariah Indonesia Periode 2019-2021 - Shofia Annisa Ratnasari; Nining Kurniasih; Yuyun Yuningsih (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Working capital can be interpreted as funds that must be available to finance the company's daily operations. This study aims to examine the effect of temporary syirkah funds and other comprehensive income on capital performance in Islamic Banks in Indonesia during the 2019-2021 period. The method used in this study is a quantitative method using secondary data from monthly financial reports and obtaining as many as 36 samples. The data analysis method used is descriptive statistical testing, classical assumption testing, and multiple analysis testing with the help of the SPSS 29 program. The results of this study show; (1) temporary syirkah funds partially have a significant effect on capital performance at PT Bank Syariah Indonesia for the 2019-2021 period; (2) other comprehensive income partially have a significant effect on capital performance at PT Bank Syariah Indonesia for the 2019-2021 period; and (3) temporary syirkah funds and other comprehensive income simultaneously have a significant effect on capital performance.